Težave pri prevajanju svetniških imen - Štavbar, Simon (Slavia Centralis, 2020)
DIFFICULTIES IN TRANSLATION OF SAINTS’ NAMES The topic of this article is translation of saints’ names from Slovenian into German and English, and of churches and artistic works dedicated to saints. The translation of saints’ names and specifc features of names are described. Translation options are suggested for names and certain regional names of churches and artistic works dedicated to saints in English and German. They are based on the frequent and evident errors (semantic and grammatical) found in selected guides, reference works, and on the Internet. Due to the complexity of this topic, it is necessary to stress the importance of knowledge and the consistency necessary for this kind of translation, and to encourage further research.